LEARNING AWARD TERHADAP PENINGKATAN KOMPETENSI DAN KINERJA KARYAWAN DEPARTEMEN QUALITY DI PT. UNILEVER INDONESIA (ULI), TBK. - SARAH NURIL, ATQIYYAH (Jurnal Akuntansi AKUNESA, 2016)
This research intends to improve comprehension about the application of Learning Award to the improvement of employee competency and employee performance in PT. Unilever Indonesia (ULI), Tbk. This research is explanatory research uses qualitative approach. This research using employees of Quality Control Department as object. Methods of datas collection to obtain data is, interview and document analysis. The result of this research is explanation of Learning Award in Quality Control department and its affect to employee which are improvement of competency and improvement of performance.